Detection of disability worsening in relapsing‐remitting multiple sclerosis patients: a real‐world roving Expanded Disability Status Scale reference analysis from the Italian Multiple Sclerosis Register. (6th November 2020) - Lepore, V.; Bosetti, C.; Santucci, C.; Iaffaldano, P.; Trojano, M.; Mosconi, P.; ,
Abstract : Background and purpose: In relapsing‐remitting multiple sclerosis patients (RRMS) disability progressively accumulates over time. To compare the cumulative probability of 6‐month confirmed disability‐worsening events using a fixed baseline or a roving Expanded Disability Status Scale (EDSS) reference, in a real‐world setting. Methods: A cohort of 7964 RRMS patients followed for 2 or more years, with EDSS scores recorded every 6 months, was selected from the Italian Multiple Sclerosis Register. The overall probability of confirmed disability‐worsening events and of confirmed disability‐worsening events unrelated to relapse was evaluated using as reference a fixed baseline EDSS score or a roving EDSS score in which the increase had to be separated from the last EDSS assessment by at least 6 or 12 months. Results: Using a fixed baseline EDSS reference, the cumulative probability of 6‐year overall confirmed disability‐worsening events was 33.2%, and that of events unrelated to relapse was 10.9% (33% of overall confirmed disability‐worsening events). Using a roving EDSS, the proportions were respectively 35.2% and 21.3% (61% of overall confirmed disability‐worsening events). Conclusions: In a real‐world setting, roving EDSS reference scores appear to be more sensitive for detecting confirmed disability‐worsening events unrelated to relapse in RRMS patients. Abstract : A cohort of 7964 relapsing‐remitting multiple sclerosis patients (RRMS) followed for 2 or more years, with Expanded Disability Status Scale (EDSS) scores recorded every 6 months, was selected from the Italian Multiple Sclerosis Register to compare the cumulative probability of 6‐month confirmed disability‐worsening events using a fixed baseline or a roving EDSS reference. Using a roving EDSS reference method, the 6‐ and 10‐year cumulative probabilities of worsening events unrelated to relapses almost doubled. In this real‐world setting, in RRMS patients, roving EDSS reference scores appear to be more sensitive for detecting confirmed disability‐worsening events unrelated to relapse.